Evaluation of the Quality of Academic Programs from the Perspective of Students in the College of Arts and Social Sciences at Sultan Qaboos University - Abdalla, Suliman Zakaria Suliman; Al-Belushi, Mohammed Ali K.; Al-Hooti, Nawal Ahmed; Al-Rashdi, Fathiya Abdulla (Dirasat: Educational Sciences, 2024)
Objectives: This study assesses the quality of academic programs in the College of Arts and Social Sciences at Sultan Qaboos University from the students’ perspective. It examines variations in perceived program quality among the college’s scientific departments. Methods: The study employs a descriptive survey approach, utilizing a questionnaire with 48 items across five dimensions to gauge the quality of academic program performance from the perspective of first-stage undergraduate students. A five-point Likert scale measures students’ attitudes. The study population comprises all first-stage undergraduate students with a minimum of 75 credited hours across various programs, totaling 761 students for the spring semester of 2020. It consists of 336 students. Results: The overall evaluation of the quality of academic programs in the college, from the students’ perspective, was rated as "moderate." It revealed that the quality levels of academic programs in the departments of Media, Arabic Language and Literature, English Language and Literature, and Geography were higher than the remaining departments: History, Information Studies, Tourism, Music, and Musicology. It identified significant differences in response means across all dimensions of academic program quality based on scientific department. No statistically significant differences were found in student responses across quality dimensions when considering the variable of gender. Conclusions: The study suggests implementing targeted programs in scientific departments to maximize the advantages of academic accreditation and improve academic program quality. It also recommends creating effective monitoring programs to address feedback from accreditation bodies and international evaluators, focusing on identifying strengths, weaknesses, and optimal methods for enhancement.